The Role of Gut Microbiota in Duodenal-Jejunal Bypass Surgery-Induced Improvement of Hepatic Steatosis in HFD-Fed Rats - Gao, Yi; Zhang, Jia; Xiao, Xiao; Ren, Yifan; Yan, Xiaopeng; Yue, Jing; Wang, Tieyan; Wu, Zheng; Lv, Yi; Wu, Rongqian (Frontiers in Cellular and Infection Microbiology, 2021)
Bariatric surgery including duodenal-jejunal bypass surgery (DJB) improves insulin sensitivity and reduces obesity-associated inflammation. However, the underlying mechanism for such an improvement is still incompletely understood. Our objective was to investigate the role of the gut microbiota in DJB-associated improvement of hepatic steatosis in high fat diet (HFD)-fed rats. To study this, hepatic steatosis was induced in male adult Sprague-Dawley rats by feeding them with a 60% HFD. At 8 weeks after HFD feeding, the rats were subjected to either DJB or sham operation. HFD was resumed 1 week after the surgery for 3 more weeks. In additional groups of animals, feces were collected from HFD-DJB rats at 2 weeks after DJB. These feces were then transplanted to HFD-fed rats without DJB at 8 weeks after HFD feeding. Hepatic steatosis and fecal microbiota were analyzed at 4 weeks after surgery or fecal transplantation. Our results showed that DJB alleviated hepatic steatosis in HFD-fed rats. Fecal microbiota analysis showed that HFD-fed and standard diet-fed rats clustered differently. DJB induced substantial compositional changes in the gut microbiota. The fecal microbiota of HFD-fed rats received fecal transplant from DJB rats overlapped with that of HFD-DJB rats. Treatment of rats with HFD-induced liver lesions by fecal transplant from DJB-operated HFD-fed rats also attenuated hepatic steatosis. Thus, alterations in the gut microbiota after DJB surgery are sufficient to attenuate hepatic steatosis in HFD-fed rats. Targeting the gut microbiota could be a promising approach for preventing or treating human NAFLD.